GEOGRAFI KEPURBAKALAAN INDONESIA - Nurhadi Rangkuti (Berkala Arkeologi, 2003)
This paper deals with the archaeological geography of Indonesia, the contents of which include the characteristics of archaeological remains, their distribution, and their relation to the environment. The final objective of this paper is to identify disaster-prone sites (natural and human) through mapping of archaeological sites and their landscapes throughout Indonesia.